Analysis of the Determinants of Islamic Social Reporting with Debt to Equity Ratio as a Moderating Variable - Purwaningsih, Febi Wulandari (Institut Agama Islam Negeri Kendari, 2023)
This research aims to see the influence of Company Size, Financing To Deposit Ratio, and Profitability on Islamic Social Reporting by adding Debt To Equity Ratio as a moderating variable. This research is a type of quantitative secondary data research, namely Sharia Banking 2016-2020. There were 10 Sharia Commercial Banks as samples in the research, which were obtained using the purposive sampling method with criteria determined by the researcher. For final results, researchers used Moderate Regression Analysis (MRA). The data analysis tool uses the E-Views 9 application. The research results show that company size influences Islamic Social Reporting. Financing To Deposit Ratio and Profitability do not affect Islamic Social Reporting. Then, the Debt To debt-equity ratio is also unable to moderate Company Size and Financing To Deposit Ratio. However, the Debt To debt-to-equity ratio is able to moderate the profitability of Islamic Social Reporting. It is hoped that this research can be a source of information for financial institutions or Islamic banks to be more careful in their social and environmental activities.